Improving Floor Gymnastics Skills in the Tiger Jump Using Rope-Assisted Media Among Grade XI Students at SMA Negeri 7 Malang - Gilang Muhammad Anwar; Febrita Paulina Heynoek; Sunarko (Journal Coaching Education Sports, 2026)
This study examines the interest of secondary school students in sports and physical activities. Adolescence is a critical period characterized by physical and psychological changes, affecting students’ motivation and engagement in extracurricular activities, including sports. The study aims to analyze the level of participation in physical activities among students and identify the factors influencing their involvement. A questionnaire-based survey was conducted among 375 students (182 females, 193 males) aged 15–20 years from four secondary schools. The results indicate a declining trend in active sports participation with increasing age, with 82% of female students and 75% of male students engaging in at least one sport under professional supervision. However, 18% of females and 25% of males do not participate in organized sports. Additionally, 97% of females and 90% of males meet the recommended level of physical activity for a healthy lifestyle, including recreational activities. The findings highlight the importance of physical education teachers in motivating students and implementing innovative approaches to increase engagement. While male students predominantly prefer team sports such as football, female students favor individual activities like dance, fitness training, and swimming. The study suggests that enhancing physical education through attractive, diverse, and modern teaching methods could foster greater participation in sports and physical activities among adolescents.